Uttarakhand Third Five Year Plan Brief Progress Report 1963-64 (Third Quarter October-December) - Government of Uttarakhand (Government of Uttarakhand, 1964)
The Uttarakhand Third Five-Year Plan Progress Report (1963–64) highlights key achievements across agriculture, infrastructure, health, education, and community welfare. Horticulture initiatives distributed over 30,000 kg of fruit plants, produced 1.76 million kg of vegetables, and trained 2,000 growers. Minor irrigation and flood control projects progressed with a revised budget of Rs. 55.84 lakhs, while soil conservation and forest development covered 168 acres. Veterinary services treated tens of thousands of animals, and breeding programs expanded. Investments in electricity, industries, transport, drinking water, sanitation, and primary education improved access and quality. Health services, including TB treatment and maternity care, strengthened public welfare, reflecting a comprehensive approach to regional socio-economic development.
Uttar Pradesh
Uttar Pradesh
Keywords: Uttarakhand; State Plan; Horticulture; Irrigation; Flood Control; Forestry; Animal Husbandry; Education; Health; Community Development; Infrastructure; Transport